Hand-in-hand quantum dot assembly sensitized photocathodes for enhanced photoelectrochemical hydrogen evolution. Issue 45 (6th November 2019) - Wu, Hao-Lin; Li, Xu-Bing; Wang, Yang; Zhou, Shuai; Chen, Ya-Jing; He, Xiao-Jun; Tung, Chen-Ho; Wu, Li-Zhu
Abstract : A hand-in-hand QD assembly sensitized photocathode with extended light absorption and oriented charge transfer is established for enhanced PEC water splitting, which is comparable to or even better than those external cocatalyst-assisted systems. Abstract : Controllable construction of quantum dot (QD)-sensitized photocathodes with simultaneously enhanced light absorption as well as efficient charge separation and oriented migration at the electrode interface is still a big challenge in photoelectrochemical (PEC) hydrogen evolution. Here, for the first time, a hand-in-hand assembly of QDs is introduced to fabricate a co-sensitized photocathode. Due to the complementary visible-light absorption and the typical type-II staggered band-position alignment between CdSe and CdTe QDs, this assembled framework not only integrates functions of the individual constituent QDs in light harvesting, but also realizes efficient charge separation and directional charge migration at the electrode interface. Compared to single-variety QD, physically mixed QD, traditional core/shell QD and sequential deposition QD photocathodes under identical conditions, the assembled system gives a much higher photocurrent density of up to −140 µA cm −2 for H2 evolution from neutral water. This work provides not only a promising toolkit for the sensitization of PEC systems with QD assemblies, but also new insights about photo-carrier modulation for future innovation, especially in establishing highly efficient artificial photosynthetic systems for feasible solar-to-fuel conversion.